2003
DOI: 10.1016/s0092-8674(03)00316-7
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin Ligase Activity in the DDB2 and CSA Complexes Is Differentially Regulated by the COP9 Signalosome in Response to DNA Damage

Abstract: Nucleotide excision repair (NER) is a major cellular defense against the carcinogenic effects of ultraviolet light from the sun. Mutational inactivation of NER proteins, like DDB and CSA, leads to hereditary diseases such as xeroderma pigmentosum (XP) and Cockayne syndrome (CS). Here, we show that DDB2 and CSA are each integrated into nearly identical complexes via interaction with DDB1. Both complexes contain cullin 4A and Roc1 and display ubiquitin ligase activity. They also contain the COP9 signalosome (CSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
743
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 670 publications
(779 citation statements)
references
References 37 publications
29
743
1
6
Order By: Relevance
“…A recent crystallographic analysis demonstrated that the binding of UV-DDB to UV lesions is entirely mediated by the DDB2 subunit, which accommodates the crosslinked pyrimidines into a specialized binding pocket and inserts a three-amino acid hairpin into the DNA minor groove [62]. DDB1, on the other hand, is an adaptor that connects the Cul4A-RBX1 ubiquitin ligase 15 to WD40-repeat target proteins [63,64], including DDB2 itself [65,66]. Other known substrates of the Cul4A-RBX1-DDB1 ubiquitin ligase include XPC [67] as well as the core histones H2A, H3 and H4 [68,69].…”
Section: The Special Case Of Cpd Recognitionmentioning
confidence: 99%
“…A recent crystallographic analysis demonstrated that the binding of UV-DDB to UV lesions is entirely mediated by the DDB2 subunit, which accommodates the crosslinked pyrimidines into a specialized binding pocket and inserts a three-amino acid hairpin into the DNA minor groove [62]. DDB1, on the other hand, is an adaptor that connects the Cul4A-RBX1 ubiquitin ligase 15 to WD40-repeat target proteins [63,64], including DDB2 itself [65,66]. Other known substrates of the Cul4A-RBX1-DDB1 ubiquitin ligase include XPC [67] as well as the core histones H2A, H3 and H4 [68,69].…”
Section: The Special Case Of Cpd Recognitionmentioning
confidence: 99%
“…The CSA gene (cloned in 1995) is located on chromosome 5q12-q13, and the gene product, which consists of 396 amino acids, belongs to the "WD repeat" family of structural and regulatory proteins that lack enzymatic activity by itself (Henning et al, 1995). The CSA protein is part of a multisubunit ubiquitin ligase complex, containing Cullin 4A, Roc 1 (Rbx1) and DNA damage binding protein 1 (DDB1) (Groisman et al, 2003). However, detailed literature on CSA is still relatively sparse.…”
Section: Mutations Causing Csmentioning
confidence: 99%
“…The isopeptide bond was formed between the C-terminal G 76 residue of Nedd8 and the ε-NH 2 group of K 720 of Cul1 (see Material and Methods). The peptide was specifically synthesized, because the MPN + -based deneddylating activity of CSN5 prefers isopeptide bonds [7]. The Nedd8-Cul1-pep was added after 1 h pre-incubation together with the caspase inhibitor z-DEVD.…”
Section: Caspase Cleavage Of Csn6 Is Accompanied By Cleavage Of Rbx1mentioning
confidence: 99%
“…As it has been shown, CSN-mediated deneddylation prevents the assembly of a specific CRL [4]. In cooperation with the UPS the CSN participates in processes such as DNA repair [7], cell cycle [8], angiogenesis [9] and development [10][11][12]. However, its role in apoptosis is unknown.…”
Section: Introductionmentioning
confidence: 99%